TANAH ULAYAT SEBAGAI SIMBOL EKSISTENSI ADAT-ISTIADAT: Studi Kasus tentang Konflik Tanah Ulayat di Perbatasan Republik Indonesia (RI) dan Republik Demokratik Timor Leste (RDTL) Segmen Bijael Sunan/Oelnasi - Elpius Kalembang (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Border Conflict between RI-RDTL Bijaelsunan/Oelnasi Segment in Manusasi Village is a claim on Ulayat Land. Various settlement efforts have been made but have not satisfied the two conflicting groups, the division of zones into the disputed area, raises new problems, for without considering the ownership of customary land, such as the local customary agreement. This study aims to analyze the conflicts, resolutions that have been implemented and formulate the conflict resolution model of RI-RDTL border. The method used in this research is descriptive qualitative with explorative approach. This study provides a model of social capital based conflict resolution that is through Baefeto-Baemone local wisdom, between the two conflicting groups. Reconciliation based on local wisdom means reconciliation is based on an accurate understanding of border history, and is based on traditional adat speeches and traditional speeches that have supernatural powers. The medium used in actualizing Baefeto baemone reconciliation through the rites that accompany the season cycle. These moments make it possible to greet each other, build the dialogues as described in the above season cycle rituals, including when gathered in traditional ceremonial events. In the process it is not allowed any coercion or political interests and with a sense of kinship (baefeto baemone) to reconciliation of conscience.